A reflection on the state of sport coaching research, its community, and representation: The 2020 International Council for Coaching Excellence Research Committee Consultation - North, J.; Callary, B.; Dieffenbach, K.; Galatti, L.; Lara-Bercial, S.; Nash, C.; O`Connor, D. (International Sport Coaching Journal, 2021)
This article provides an overview of the context, details, and outcomes of a consultation and review of the International Council for Coaching Excellence`s interactions and engagements with, and service provision to, the international sport coaching research community. The consultation and review were undertaken by the International Council for Coaching Excellence Research Committee (RC). The paper starts with a description of the sport coaching research landscape. It then provides details of the role of the International Council for Coaching Excellence, its Research Fair, and RC. The paper then offers an overview of the formal initiation of the consultation and review at the Global Coach Conference, Japan 2019, as well as a brief overview of the approach used. It then details the consultation findings providing direction for the RC moving forward. The resultant revised RC terms of reference are included as an appendix.